Worldwide fertility declines do not rely on stopping at ideal parities. (2nd January 2019) - Hruschka, Daniel J.; Sear, Rebecca; Hackman, Joseph; Drake, Alexandria
Abstract : A key demographic hypothesis has been that fertility declines rely on stopping at target parities, but emerging evidence suggests that women frequently reduce fertility without specific numeric targets. To assess the relative importance of these two paths to fertility decline, we develop a novel mixture model to estimate: (1) the proportion of women who stop at a target parity; and (2) mean completed fertility among those who do not. Applied to Demographic and Health Survey data from women aged 45–49 in 84 low- and middle-income countries, and to United States Census cohorts, the model shows considerable variation in the proportion stopping at specific parities (1–84 per cent). The estimates also show that declines in completed fertility are largely attributable to women who do not stop at target parities, suggesting that stopping at ideal parities may be less important than parity-independent decisions for a wide range of fertility transitions.